Sedentary behaviours of girls and boys aged 7-15 - Czaprowski, Dariusz; Stoliński, Łukasz; Szczygieł, Andrzej; Kędra, Agnieszka (Polish Journal of Public Health, 2011)
Introduction. Sedentary behaviours are in opposition to physical activity. An improper balance between them leads to the spreading of numerous health disorders in children and youth. Thus, it is significant to observe sedentary behaviours and factors which determine them in order to undertake proper prophylactic and therapeutic activities. The aim of the work was to define the amount of time spent by girls and boys aged 7-15 on sedentary behaviours and to evaluate differences concerning their levels between both genders. Material and methods. The group under research included 273 girls and 323 boys aged 1-6 of primary school and aged 1-3 of lower secondary school. Method: diagnostic poll (tool: questionnaire). The data collected were analysed statistically with the use of the software Statistica 7.1. (Stat Soft, USA). Results. Girls spent 83.8 (±25.2) hours while boys 81.2 (±21.0) hours per week on sedentary behaviours (p>0.05). It was observed that with age total time devoted to all sedentary activities and time spent at school, learning and using a computer lengthened. Boys spent significantly more time using a computer, whereas girls devoted considerably more time to learning, reading and drawing. The analysis revealed a significant relationship between gender, year at school and an average number of hours spent on particular sedentary behaviours only as far as time devoted to after-school learning is concerned.Conclusions. • Time devoted by children and youth to sedentary behaviours lengthens systematically with age.• Time devoted to learning, reading, drawing and using a computer is determined by the gender of children and youth.• While planning sports and recreational activities for children and youth, types of sedentary behaviours must also be defined.